Pengaruh Gadget pada Minat dan Hasil Belajar Siswa Kelas II SDN 67 Pekanbaru - Nadia; Febrina Dafit (Journal for Lesson and Learning Studies, 2022)
Almost all students in second grade can already use gadgets such as to play games and watch YouTube videos and TikTok. It makes students' interest in learning decrease and their learning outcomes decrease. This study aimed to determine the effect of gadgets on interest in learning and the effect of gadgets on learning outcomes of second-grade elementary school students. This research belongs to the quantitative descriptive research with the research population, namely the second-grade elementary school students, totaling 38 students. Sampling in the study was carried out using a saturated sampling technique, with a final sample size of 38 students. The data collection in this study was carried out using the method of observation, interviews, and questionnaires, with the research instrument in the form of a Gadget Variable Questionnaire (X1) with 25 statement items and a Learning Interest variable questionnaire (Y1) with 23 statement items. The data obtained in this study were then analyzed using normality, homogeneity, simple linear regression, and correlation of determination. The results of the simple regression test show that Gadget (X) has an influence on learning interest (Y1) by 14.2%, and the result of Gadget (X) has an effect on learning outcomes (Y2) by 10.9% in second-grade students at SD Pekanbaru. This study concludes that gadgets affect students' interest in learning and learning outcomes.